Smartcard, Shop, Belanja, Sistem PROTOTYPE “SMARTCARD SHOP” UNTUK TRANSAKSI BELANJA DIGITAL - Joni Maulindar; Nurohman Nurohman (Universitas PGRI Yogyakarta, 2020)
The process of meeting the needs of everyone is important. Various shopping places visited to carry out buying and selling activities in the place. However, not a few problems encountered from the process. The number of groceries purchased will be very troublesome for customers, the transaction process will also be a problem. The purpose of this research is to make a smartcardshop system planning concept for shopping without a long time. The analysis is conducted to find out the weaknesses of the transaction process carried out by people who buy at a store. The data obtained is made as a basis for developing the system so that buyers can make the purchase process quickly using RFID for each product to be purchased. The method used in this study uses two methods. The first method is that researchers use data collection methods, among others, by collecting data from resource persons consisting of problems experienced when a product purchase transaction is carried out. In addition, product data is also collected to support the information system design process. The second method is the researcher uses the system development method in this case the researcher uses the prototype method. The results of this study are the concept and design of a smartcard shop information system to shop without using RFID for a long time.